IMPROVING CHILDREN READING SKILL THROUGH PICK AND PLAY MEDIA - Novianti, Ria (Proceeding 7th International Seminar on Regional Education, 2015)
AbstrakReading is one of the important skill that children should master. In Early Childhood Education children start to learn reading from simple steps according to their developmental stages. The aim of this study is to determine wether the pick and play media can improve the reading skill of 24 children aged 5-6 years-old in group B TK Laboratorium FKIP Unri. This research used the experimental research method with one sample test. Research is carried out by observation, interview and documentation. The result of T-Test show that there is a significant difference and the result of data analysis show pretest score is 54,17% or in medium category and post test score is 80,36% or in good category. It indicates the increasing of children reading skill is about 26,19%. That means that the use of pick and play media can improve children reading skill. It implies that the pick and play visual media can be usefull for early childhood education teachers and also parents in helping children explore and developing their reading skill from the very begining because the right and interactive reading media will lead to the acquasition of reading skill in children.Keywords: reading skill, visual media